2011
DOI: 10.1080/02640414.2010.523088
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of visual and auditory feedback to control the running mechanics of well-trained athletes

Abstract: The correlation between mechanical factors of running and running economy as measured by metabolic cost is a subject of much interest in the study of locomotion. However, no change in running technique has been shown to result in an immediate improvement in running economy on an intra-individual basis. To evaluate the effect of a modified running technique, it is probably necessary that the individual trains with the new technique for a longer period using a feedback system to control the new kinematics. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 30 publications
3
58
0
2
Order By: Relevance
“…Studies on data sonification have revealed that changes in numerical values are preferably not mapped to loudness changes, in order to minimize concerns about interactions between pitch and loudness (Neuhoff, Kramer, & Wayand, 2002). However, studies on error sonification have successfully mapped the total amount of deviation with respect to a target movement to loudness (Drobny et al, 2009;Eriksson et al, 2011;Godbout & Boyd, 2010;Kleimann-Weiner & Berger, 2006;Vogt, Pirró, Kobenz, Höldrich, & Eckel, 2010).…”
Section: Design Aspects Of Auditory Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on data sonification have revealed that changes in numerical values are preferably not mapped to loudness changes, in order to minimize concerns about interactions between pitch and loudness (Neuhoff, Kramer, & Wayand, 2002). However, studies on error sonification have successfully mapped the total amount of deviation with respect to a target movement to loudness (Drobny et al, 2009;Eriksson et al, 2011;Godbout & Boyd, 2010;Kleimann-Weiner & Berger, 2006;Vogt, Pirró, Kobenz, Höldrich, & Eckel, 2010).…”
Section: Design Aspects Of Auditory Feedbackmentioning
confidence: 99%
“…In complex tasks, visual feedback has also been provided by abstract visualizations (Crowell & Davis, 2011;Debaere, Wenderoth, Sunnaert, Van Hecke, & Swinnen, 2003, 2004Eaves et al, 2011;Eriksson et al, 2011;Hurley & Lee, 2006;Kovacs & Shea, 2011;Lee et al, 1990;Lee, Swinnen, & Verschueren, 1995;Maslovat et al, 2009;Smethurst & Carson, 2001;Snodgrass et al, 2010;Swinnen et al, 1998;Swinnen et al, 1997;Wishart et al, 2002;Wulf et al, 1999;Wulf et al, 1998). For complex interlimb coordination tasks, a displacement-displacement plot (Lissajous figure) has been used in many studies as an abstract concurrent feedback (Debaere et al, 2003(Debaere et al, , 2004Kovacs & Shea, 2011;Maslovat et al, 2009;Ronsse, Puttemans, et al, 2011;Smethurst & Carson, 2001;Swinnen et al, 1998;Swinnen et al, 1997).…”
Section: Abstract Visualizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent and innovative study demonstrated that a combination of visual and auditory feedback provided in real-time, was able to influence vertical displacement and step frequency during treadmill running at 16 km.h -1 . 6 This finding suggests that augmented feedback could be an effective method for controlling or inducing changes in motor performance during a task requiring rapid and repetitive movement.…”
Section: Introductionmentioning
confidence: 97%
“…There are numerous variables such as mechanical work during running 6 that are commonly used in human movement A c c e p t e d M a n u s c r i p t 5 studies. Measures which may describe performance in a motor task may also include spatiotemporal and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%